Risk factors for multidrug-resistant pseudomonas aeruginosa among Hospitalized Patients at a Malaysian Hospital - Mohd Nasir, M.D.; Nurnajwa, M.H.; Lay, J.; Teoh, J.C.; Syafinaz, A.N.; Niazlin, M.T. (Universiti Kebangsaan Malaysia, 2015)
A case-control study was conducted based on medical cases of 100 hospitalized patients with Pseudomonas aeruginosa-isolation at a Malaysian hospital. Cases with 50 multidrug-resistant P. aeruginosa MDRPA and 50 non-multidrug-resistant P. aeruginosa (NMDRPA) were randomly included and compared with socio-demographic and clinical data of the patients, using Chi-square and Fisher’s exact tests as the statistical tool. Analysis found no significant association between MDRPA with ages, gender and ethnicity of patients (p>0.050). Other risk factors being investigated were invasive procedure, immunosuppression, bedridden and clinical diagnosis such as central nervous- and respiratory-system disorder, as well as antibiotic exposure during hospitalization and duration of hospital stay with only the last two were found to have significant association (p=0.035 and 0.019, respectively). Some other studies also reported a similar association indicating that the two factors could serve as an important predictive tool for isolation of MDRPA. More studies involving a larger sampling size are warranted to establish the association.